Ojačitve lesenih nosilcev - Wallner, Edo (AR. Arhitektura, raziskave, 2004)
There are numerous methods used for strengthening wooden beams, depending on given circumstances and possibilities. Wooden beams can be strengthened before or after assembly, when the beam is already in place and under loads. To stimulate the development of time-conditioned deformations and stress in wood we produced the computer programme Scout, which facilitates simulation of additional glued lamellas of various materials and even pre-bending technology. When simulating materials we can specify any given material, even such with non-linear response, including creeping. In the research we conducted several comparative simulations, and used them to test the programme. Numerical results from the programme and experimental data gathered from literature were relatively similar. We proved that additional glued lamellas were beneficial against stretching and that pre-stressing done with the pre-bending technology actually enhanced the effect of strengthening. Therefore we proved that the same effect could be achieved with less material.
Keywords: konstrukcije; nosilci; leseni nosilci; predkrivljenje; lepljen lameliran les; raziskave